Transformasi Sistem Pemerintahan di Jawa Barat: Analisis Historis dan Nilai Kearifan Lokal di Gedung Sate - Sri Atiah, Elis; Triani, Ani; Lestari, Sri Ayu; Rajasa, Mikail Baskara; Darojat, Arik (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This research analyzes the tranformation of the governmentt system in west Java, focusing on Gedung Sate at a symbol of governance and culture. Built during the Dutch colonial period, Gedung Sate serves not only as an administrative center but also as a historical landmark reflecting Sundanese local wisdom. Using a descriptive qualitative approach and a case study design, this study explores historical phases, including the Hindu-Buddhist kingdoms, Dutch colonialism, Japanese occupation and the modern era. This transformation encompasses policy evolution and the integration of local wisdom values, such amutual cooperation (gotong royong) and community participation, into public administration processes. The findings reveal that incorporating cultural values into policies at Gedung Sate enhances government-community relations and reinforces Wesst Java’s cultural identity amidst modernization.